POTENTIAL REUSE OF WASTEWATER BY UTILIZING NANO-FILTRATION TECHNIQUE-A RESEARCH PAPER - Muhammad Waqas Ahmed Saleem,; Adeel Ur Rehman,; Muhammad Aamir,; Muneeb Ur Rehman,; Qadeer Ahmaed,; Abdullah Solangi,; Shan Tariq,; Fakhar Ammar Haider, (Spectrum of Engineering Sciences, 2025)
The generation of wastewater from human activities is an inevitable consequence of urbanization and industrialization. In Pakistan, where water scarcity is exacerbated by aging infrastructure and increasing demand, the development of cost-effective and efficient water treatment technologies is crucial. Conventional wastewater treatment plants (CWWTPs) are often limited by high construction and maintenance costs, as well as significant land requirements. This study evaluates the performance of nanofiltration (NF) membranes for wastewater treatment as a sustainable alternative. A pilot-scale NF system using hollow fiber membranes with a pore size of 0.002 µm was employed to assess the removal efficiency of key water quality parameters, including biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), total dissolved solids (TDS), turbidity, hardness, and pH. Experiments were conducted at pressures ranging from 4 to 10 bars, with optimal performance observed at a filtration time of 15–20 minutes and a flux rate of 20 L/m²·h using undiluted wastewater. Results indicated a marked improvement in treatment efficiency with increasing operating pressure, demonstrating the potential of direct NF treatment in reducing contaminants effectively while minimizing infrastructure demands.